Microwave-assisted dyeing of poly(butylene terephthalate) fabrics with disperse dyes - ÖNER, ERHAN (WILEY-BLACKWELL, 2013)
In this study, conventional heating and microwave dielectric heating in the exhaust dyeing of poly(butylene terephtalate) fabrics with disperse dyes were studied in order to determine whether microwave heating could be used to increase the dyeability of poly(butylene terephtalate) fibre in shorter processing times and enable dyeings of adequate wet fastness to be obtained. Accordingly, the samples of 100% poly(butylene terephtalate) single jersey knitted fabric were dyed with CI Disperse Yellow160 and CI Disperse Yellow42, CI Disperse Red177 and CI Disperse Red91, CI Disperse Blue79:1 and CI Disperse Blue54 at 98 degrees C with or without microwave dielectric heating. The colouristic properties, colour fastnesses and the tensile properties of the dyed fabrics were investigated and compared with each other. Microwave dielectric heating is regarded as a tool for green chemistry' and provides many advantages over conventional heating without any deterioration in the properties of the dyed materials. Microwave heat dyeing enhances the exhaustion and the fixation of dye, and good colour fastnesses and repeatability in dyeings are achieved in short heating times of the dyebath.
Keywords: COTTON FABRICS; EASY CARE; POLYESTER; FIXATION; IRRADIATION; DIFFUSION; MOLECULES; BEHAVIOR; FIBER